2021
DOI: 10.3390/agriculture11121190
|View full text |Cite
|
Sign up to set email alerts
|

Using Channel and Network Layer Pruning Based on Deep Learning for Real-Time Detection of Ginger Images

Abstract: Consistent ginger shoot orientation helps to ensure consistent ginger emergence and meet shading requirements. YOLO v3 is used to recognize ginger images in response to the current ginger seeder’s difficulty in meeting the above agronomic problems. However, it is not suitable for direct application on edge computing devices due to its high computational cost. To make the network more compact and to address the problems of low detection accuracy and long inference time, this study proposes an improved YOLO v3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…It is easy to achieve a trade-off between performance and parameters by adjusting the pruning rate. At the same time, layer-wise pruning is often used as an auxiliary pruning method in networks with many branches [85], [86]. Although the channel/filter-wise pruning based on reinforcement learning is time-consuming, it effectively solves the limitation of manually set magnitudes [70].…”
Section: Network Pruningmentioning
confidence: 99%
“…It is easy to achieve a trade-off between performance and parameters by adjusting the pruning rate. At the same time, layer-wise pruning is often used as an auxiliary pruning method in networks with many branches [85], [86]. Although the channel/filter-wise pruning based on reinforcement learning is time-consuming, it effectively solves the limitation of manually set magnitudes [70].…”
Section: Network Pruningmentioning
confidence: 99%
“…Channel pruning is also one of the ideas of the model lightweight, to build a lightweight detection model for apple fruitlet pre-thinning, Dandan Wang et al [24] conducted channel pruning based on YOLOv5s, which reduced the number of parameters by 92.7% while maintaining the accuracy of detection. Fang L et al [25] built a lightweight model by pruning the redundant channel and network layers of the YOLOV3 model, and realized real-time monitoring of ginger sprouts and seeds with a map of 98.0%, greatly optimizing the model size and detection time.…”
Section: Model Lightweightmentioning
confidence: 99%
“…The improved model outperformed base YOLOv5 in precision in identifying flower, green, and red tomatoes by 17%, 2%, and 2.3%, respectively, with a decreased model size of 10.5 MB. Fang et al [13] suggested an improved YOLOv3 model to detect ginger shoots and seeds in real-time, which significantly compresses network size and improves inference time by pruning redundant channels and network layers. The results suggest a decrement in model size by 87.2%, an increase in detection speed by 85%, and mAP lagging slightly by 0.1%.…”
Section: Introductionmentioning
confidence: 99%